2011
DOI: 10.5732/cjc.010.10529
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy in clinical practice

Abstract: Radiation dose escalation and acceleration improves local control but also increases toxicity. Proton radiation is an emerging therapy for localized cancers that is being sought with increasing frequency by patients. Compared with photon therapy, proton therapy spares more critical structures due to its unique physics. The physical properties of a proton beam make it ideal for clinical applications. By modulating the Bragg peak of protons in energy and time, a conformal radiation dose with or without intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 58 publications
(80 reference statements)
0
51
0
1
Order By: Relevance
“…PBS of proton beams allows for highly conformal treatment deliveries, minimizing dose to surrounding tissue (Saini et al, 2017, Liu andChang, 2011). This is accomplished by careful placement of spots tightly around the target volume in a way that limits dose to healthy tissue (Liu and Chang, 2011). However, other proton beam delivery techniques, such as passive scattering, employ aperture collimation that allows for sharper lateral penumbra than PBS without apertures.…”
Section: Introductionmentioning
confidence: 99%
“…PBS of proton beams allows for highly conformal treatment deliveries, minimizing dose to surrounding tissue (Saini et al, 2017, Liu andChang, 2011). This is accomplished by careful placement of spots tightly around the target volume in a way that limits dose to healthy tissue (Liu and Chang, 2011). However, other proton beam delivery techniques, such as passive scattering, employ aperture collimation that allows for sharper lateral penumbra than PBS without apertures.…”
Section: Introductionmentioning
confidence: 99%
“…Bu uygulamalar arasında glioblastoma, hipofiz adenomları, serebral arteriyo-venöz anevrizmalar, kafa tabanı sarkomları ve uveal melanomlar bulunmaktadır. [5] Hastane temelli proton tedavisi 1990'da Loma Linda Üniversite-sinde başlamış ve 2008 yılı sonuna kadar yaklaşık 13 bin hasta tedavi edilmiştir. [6] 2001'de MGH'de, 2006'da MD Anderson kanser merkezinde proton tedavi merkezleri faaliyete geçmiştir.1980'lerden 2000'li yıllara kadar araştırma enstitüleri içinde veya hastane temelli olmak üzere geniş bir yelpazede büyük bir çoğrafik bölgede proton tedavisi yayılmıştır.…”
Section: Tarihiunclassified
“…Recently, studies focused on predicting patient‐specific dosimetric benefits of PT and dose escalation. For example, Liu et al . demonstrated that proton radiation dose escalation improved local control but also increased toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, studies focused on predicting patient-specific dosimetric benefits of PT 6 and dose escalation. For example, Liu et al 7 demonstrated that proton radiation dose escalation improved local control but also increased toxicity. However, the lack of identifying biomarkers for conclusive patient outcome, limits the transfer of PT into personalized medicine.…”
Section: Introductionmentioning
confidence: 99%